Rush Hour 2 - Nathanson, Jeff; Sarkissian, Arthur 1960- (Arthur M.); Birnbaum, Roger; Stern, Jay; Glickman, Jonathan; Ratner, Brett; Tucker, Chris, 1972-; Cheng, Long, 1954-; Lone, John, 1952-; King, Alan, 1927-2004; Sanchez, Roselyn, 1973-; Yulin, Harris; et al. ([United States] : New Line Home Entertainment : Warner Bros., 2001)
It's vacation time for Det. Carter and he finds himself alongside Det. Lee in Hong Kong wishing for more a little more excitement. Lee is out to track down a Triad gang lord who may be responsible for killing two men at the American Embassy in Hong Kong. Things get complicated as the pair stumble onto a counterfeiting plot between a L.A. crime boss and a Triad leader. A trip back to the U.S. may provide the answers about the bombing, the counterfeiting, and the true allegiance of a sexy customs agent.
Based on the characters created by Ross La Manna.
Special features: Jackie Chan's Hong Kong introduction; culture clash: west meets east; language barrier; attaining international stardom; kung-fu choreography; early Brett Ratner student film "Lady luck"; fast track: trivia subtitle track with direct access to additional features; deleted scenes/outtakes with optional director commentary; commentary by director Bret Ratner and writer Jeff Nathanson; "Making magic out of mire: a look at Brett Ratner"; "Evolution of a scene: analysis of selected scenes"; fashions of "Rush hour 2"; visual effects deconstruction; theatrical & teaser trailers; cast and crew filmographies: DVD-ROM features: script-to-screen; website; link to exclusive infinifilm.com; features and more!
Director of photography, Matthew F. Leonetti ; editor, Mark Helfrich ; music, Lalo Schrifrin ; costume designer, Rita Ryack ; production designer, Terence Marsh.
Chris Tucker, Jackie Chan, John Lone, Alan King, Roselyn Sanchez, Harris Yulin, Zhang Ziyi.
MPAA rating: PG-13.
Also issued on VHS.
Keywords: Vacations -- China -- Hong Kong -- Drama; Detective and mystery plays; Video recordings; Video recordings for the hearing impaired; DVD-Video discs; Drama; Feature films; Comedy films